MnTnHex-2-PyP5+, Coupled to Radiation, Suppresses Metastasis of 4T1 and MDA-MB-231 Breast Cancer via AKT/Snail/EMT Pathways - Sung-Won Shin; Changhoon Choi; Hakyoung Kim; Yeeun Kim; Sohee Park; Shin-Yeong Kim; Ines Batinic-Haberle; Won Park (MDPI AG, 2021)
Tumor migration and invasion induced by the epithelial-to-mesenchymal transition (EMT) are prerequisites for metastasis. Here, we investigated the inhibitory effect of a mimic of superoxide dismutase (SOD), cationic Mn(III) ortho-substituted N-n-hexylpyridylporphyrin (MnTnHex-2-PyP5+, MnHex) on the metastasis of breast cancer in cellular and animal models, focusing on the migration of tumor cells and the factors that modulate this behavior. Wound healing and Transwell migration assays revealed that the migration of mouse mammary carcinoma 4T1 cells was markedly reduced during the concurrent treatment of MnHex and radiation therapy (RT) compared with that of the control and RT alone. Bioluminescence imaging showed that MnHex/RT co-treatment dramatically reduced lung metastasis of 4T1 cells in mice, compared with the sham control and both single treatments. Western blotting and immunofluorescence showed that MnHex treatment of 4T1 cells reversed the RT-induced EMT via inhibiting AKT/GSK-3β/Snail pathway in vitro, thereby decreasing cell migration and invasion. Consistently, histopathological analyses of 4T1 tumors showed that MnHex/RT reduced Snail expression, blocked EMT, and in turn suppressed metastases. Again, in the human metastatic breast cancer MDA-MB-231 cell line, MnHex inhibited metastatic potential in vitro and in vivo and suppressed the RT-induced Snail expression. In addition to our previous studies showing tumor growth inhibition, this study demonstrated that MnHex carries the ability to minimize the metastatic potential of RT-treated cancers, thus overcoming their radioresistance.